Performance analysis of batch receiving wireless sensor networks with interference signals. (19th May 2021) - Fan, Jiaqi; Ma, Zhanyou; Yu, Xiangran; Zhang, Yang
In order to improve the energy efficiency, the operating situation of batch receiving wireless sensor network is discussed in this paper. Combining with environmental interference signals, repairable faults of the sensor node and other actual situation, process of receiving and transmitting data packets in wireless sensor networks is simulated. An M X /G/1 vacation queueing model with customers arriving in batches, negative customers, feedback customers, wake-up periods, optional vacations and repairable faults is established. The steady state distribution of the system is solved by using the supplementary variable method, and expressions of the energy saving rate and other performance indexes are given. The equilibrium of the system is discussed by establishing revenue function of the system. Then, using MATLAB software for numerical analysis, the influence of system parameters on performance indexes of wireless sensor networks systems is analysed, and equilibrium numerical results are obtained.